PENERAPAN PROTOKOL KESEHATAN UNTUK MEWUJUDKAN GENERASI SEHAT KAMPUNG KB PADA ERA NEW NORMAL - Bintang Narpati; Kardinah Indrianna Meutia (LPPM Universitas Bina Bangsa, 2022)
Corona Virus (Covid-19) is a virus that can spread like an outbreak and be transmitted to others caused by the SARS-CoV2 virus (MLE, 2020). Some patients affected by this virus recover without having to go to the hospital because they are categorized as having mild to moderate respiratory problems. However, there are some other patients due to the infection of the Covid-19 virus who have to get treatment in the hospital because the patient has a severe respiratory problem that requires the treatment of a medical team. Common symptoms for Covid-19 sufferers are cough, fever, sore throat, shortness of breath, etc. (Singh & Singh, 2020). The average period of the incubation period of this virus is approximately 5-6 days. With the incubation period that takes a relatively long time, it can cause an increasing mortality rate due to the Covid-19 virus (Rusdiana, 2021). Patients who have Covid-19 disease can result in acute respiratory distress syndrome (ARDS), pneumonia (pneumonia) and failure of several organs. Patients at high risk are elderly and sufferers who have a history of medical diseases such as hypertension, diabetes, heart disease, chronic respiratory diseases or cancer. The spread of this Virus through the mouth or nose of an already infected person through droplets or small liquid particles when they cough, sneeze, speak, sing or breathe. Corona Virus Disease 2019 (Covid-19) by the World Health Organization (WHO) has been designated as a global outbreak (